FIBER REINFORCED CONCRETE: PULLOUT, TOUGHNESS INDEX & APPLICATION - Faisal Sheikh Khalid; Mohd Irwan Juki (2018)
This book consists of four chapter namely Introduction, Fiber Bond and Pull out Fiber, Toughness Concrete Fiber, and Application of Fiber Reinforced Concrete. Every chapter consists of introduction, subtopic, and previous works to enhancing self-learning.